Potential of Tamarind (Tamarindus indica L.) leaves as funtional food - Dewi, Kifayati Rosiyanti; Wahyudi, Ari; Pangestuti, Meitriana (Bioculture Journal, 2025)
Background: Public interest in functional foods, which provide health benefits beyond basic nutrition, is growing in Indonesia and worldwide. Despite their recognized medicinal properties, tamarind leaves remain underutilized in functional food applications. This review examines their potential as a valuable local resource for disease prevention. Methods: A literature search on "Tamarindus indica leaf" was conducted using databases such as Scopus and Web of Science. Data were collected from sources published between 2010 to 2024, adhering to specific inclusion criteria. Analytical methods included thematic categorization and comparison of findings, with an emphasis on the health benefits and functional food potential of tamarind leaves. Finding: Tamarind leaves have been proven to have extensive functional benefits including as a source of antioxidants, antibacterial, antifungal, blood cholesterol lowering agents, antidiarrhea, antiobesity, antidiabetic, anti-inflammatory. Tamarind leaves have the potential to be processed into functional drinks and as a mixture of food products such as snacks. Conclusion: Tamarind leaves are an underutilized functional food; further research and innovation are essential for their development. Novelty/Originality of this article: There has been no publication that specifically discusses the potential of tamarind leaves as a functional food. This publication is expected to fill this knowledge gap.